A Cool, Nutrient‐Enriched Eastern Equatorial Pacific During the Mid‐Pleistocene Transition. Issue 4 (26th February 2019) - Robinson, Rebecca S.; Jones, Colin A.; Kelly, Roger P.; Rafter, Patrick; Etourneau, Johan; Martinez, Philippe
Abstract: The emergence of high‐amplitude, low‐frequency glacial‐interglacial cycles during the mid‐Pleistocene climate transition (MPT; 800–1, 200 ka) is associated with global cooling. In the eastern equatorial Pacific, sea surface temperatures cooled, and the upwelling‐induced cold tongue expanded significantly during the MPT. Here we use sedimentary records of iron, biogenic silica, and nutrient‐nitrogen consumption to evaluate biogeochemical changes hypothesized to accompany the cold tongue expansion. Our results suggest that the eastern equatorial Pacific of the MPT hosted surface waters with higher nitrate contents and biogenic silica production relative to the last 600 ka. Increased production occurred despite low iron supply. We attribute this to enhanced upwelling and nutrient enrichment of thermocline waters, both likely related to the northward migration of Southern Ocean fronts. The return of these fronts to their southward positions after the MPT may be associated with stronger drawdown of nutrients and, potentially, atmospheric CO2 in the Southern Ocean. Plain Language Summary: As the Earth's climate cooled, it also experienced a change in the frequency of ice ages around a million years ago. Ice ages became more intense and longer. In the equatorial Pacific, the transition between these two climate states is marked by a temporary expansion of cold surface water that winds deliver from below. Here we use sedimentary records to show that the expanded cold region also hosted higher nutrient concentrations and boosted biological production. The reconstructed increase in nutrient concentrations is interpreted as both an increase in the rate of nutrient supply, likely related to stronger winds, and delivery of waters bearing a higher overall nutrient concentration. Together, this implies a short‐term redistribution of nutrients in the ocean. These data also suggest that the equatorial Pacific that we think of today as cool and nutrient rich relative to the rest of the tropical Pacific is small relative to ~900, 000 years ago as a result of this shift in the climate. Key Points: Expansion of the equatorial Pacific cold tongue during the MPT accompanied expanded nutrient richness and higher export of biogenic silica The increases in production and nutrient availability are attributed to enhanced upwelling and nutrient enrichment of thermocline waters The nutrient enrichment stems from reorganization of oceanic nutrient distributions linked to migration of Southern Ocean fronts